High-barrier aluminized composite digital printed corrugated carton and production method thereof

CN122877448APending Publication Date: 2026-10-09PUER SHUIHONG PACKAGING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610797095.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-04
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

针对现有技术的不足,本发明提供了一种高阻隔镀铝复合数字印刷瓦楞纸箱,解决了现有镀铝层与纸基结合力差、抗折叠性能不足从而使阻隔性能急剧下降的问题

Benefits of technology

本发明通过在底涂层中构建微相分离结构,为纯氩等离子体选择性刻蚀提供材料学基础,实现自模板化有序纳米凹坑的形成,凹坑侧壁以残留的聚硅氧烷微区为骨架,铝原子直接填入凹坑并凝固成与凹坑形貌完全互补的铝纳米栓柱,通过纯物理机械互锁将镀铝层牢固锚固于基底,无需依赖任何化学键合或自由基反应,从根本上解决了传统镀铝瓦楞纸箱因界面结合力不足而在折叠成型和运输堆码过程中产生微裂纹扩展、导致阻隔性能衰减的技术难题,并且全体系采用水性材料,镀铝层厚度不超过50nm,纸箱使用后纤维成浆率达98.5%,满足可回收性要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122877448A_ABST
    Figure CN122877448A_ABST
Patent Text Reader

Abstract

The application discloses a high-barrier aluminized composite digital printing corrugated carton and a production method thereof, and relates to the technical field of packaging materials.The high-barrier aluminized composite digital printing corrugated carton comprises a base material, an inner barrier coating, a primer layer and an aluminized layer.The micro-phase separation structure is constructed in the primer layer to provide a material basis for selective etching of pure argon plasma, the formation of self-templating ordered nanometer pits is realized, the pit sidewall is taken as a framework of residual polysiloxane microzones, aluminum atoms are directly filled into the pits and solidified into aluminum nanostuds which are completely complementary to the pit morphology, the aluminized layer is firmly anchored to the base material through pure physical mechanical interlocking, and any chemical bonding or free radical reaction is not needed, so that the technical problem that micro-cracks are expanded during folding and forming and transportation and stacking of the traditional aluminized corrugated carton due to insufficient interfacial bonding force and the barrier performance is attenuated is fundamentally solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of packaging materials technology, specifically to a high-barrier aluminum-coated composite digitally printed corrugated cardboard box and its production method. Background Technology

[0002] Corrugated cardboard boxes are widely used in the field of commodity transportation packaging due to their advantages such as lightweight, high strength, recyclability, and low cost. With the rapid development of e-commerce logistics and cold chain transportation, the market has put forward higher requirements for the barrier performance of corrugated cardboard boxes. Existing technology can significantly improve the barrier ability against gas and moisture and extend the shelf life of contents by applying aluminum plating to the surface of the cardboard. However, in practical applications, the bonding force between the aluminum plating layer and the paper base of existing aluminum-plated corrugated cardboard boxes is poor. The interface bonding between the aluminum layer and the cardboard face paper mainly relies on physical adsorption or simple chemical anchoring. Furthermore, its folding resistance is insufficient. During the creasing, folding, or stacking of the cardboard box, bending stress can easily cause micro-cracks or even peeling of the hard and brittle aluminum plating layer, resulting in a sharp decline in barrier performance. Although traditional base coatings can provide some buffering, they cannot fundamentally inhibit the initiation and propagation of cracks.

[0003] Therefore, there is an urgent need for an aluminized corrugated cardboard box that can combine ultra-high interfacial bonding strength with excellent bending resistance to solve the problems existing in the current technology. Summary of the Invention

[0004] (a) Technical problems to be solved To address the shortcomings of existing technologies, this invention provides a high-barrier aluminized composite digitally printed corrugated cardboard box, which solves the problems of poor adhesion between the aluminized layer and the paper base, insufficient folding resistance, and thus a sharp decline in barrier performance.

[0005] (II) Technical Solution To achieve the above objectives, the present invention provides the following technical solution: a high-barrier aluminized composite digitally printed corrugated cardboard box, comprising a substrate, an inner barrier coating, a base coating, and an aluminized layer, characterized in that: The substrate is corrugated cardboard; The inner barrier coating is applied to the inner surface of the substrate using a water-based polyvinylidene chloride emulsion. The base coating is formed by coating an organosilicon-modified polyurethane-acrylate hybrid aqueous emulsion. After drying and forming a film, the organosilicon segments spontaneously migrate and accumulate towards the surface of the base coating, forming a microphase-separated structure between the polysiloxane microdomains and the polyurethane-acrylate matrix. The surface of the base coating is selectively etched by pure argon plasma to form a nano-pit array, and the corrosion-resistant polysiloxane micro-regions remain as the protruding skeleton between the nano-pits. The aluminum plating layer is deposited on the surface of the nano-pits. After aluminum atoms fill the interior of the nano-pits and solidify, they form aluminum anchors that complement the morphology of the pits. The aluminum plating layer is anchored to the nano-pits by a purely physical mechanical interlock between the sidewalls of the nano-pits and the aluminum anchors.

[0006] In some embodiments, the bond energy of the Si-O bonds in the polysiloxane microregions of the undercoating layer is higher than that of the CC and CO bonds in the polyurethane acrylate matrix, and the surface energy of the polysiloxane is lower than that of the organic matrix. This results in the intrinsic etching rate of the microregions under pure physical sputtering conditions being lower than that of the organic matrix. In the pure argon plasma process, it serves as an in-situ resist mask to achieve self-templating selective etching.

[0007] In some embodiments, the silicone segments in the base coating are hydroxyl-terminated polydimethylsiloxane, which account for 8% to 9.3% of the emulsion solid content.

[0008] In some embodiments, the depth of the nanopits is 15 nm to 30 nm, and the areal density is 10. 9 pcs / cm 2 Up to 10 10 pcs / cm 2 Magnitude.

[0009] In some embodiments, the aluminum layer thickness of the aluminum plating layer is 40 nm to 55 nm.

[0010] In some embodiments, the surface of the aluminum plating layer is provided with a passivation layer, which is a dense γ-Al2O3 type passivation layer formed by nitrogen-oxygen mixed gas atmospheric pressure plasma treatment under nitrogen protection after the aluminum plating layer exits the vacuum chamber, with a thickness of 2nm to 3nm, and the surface energy of the passivation layer can be increased to 58mN / m to 62mN / m.

[0011] In some embodiments, the passivation layer surface is provided with a digital printing layer, which is formed by inkjet printing using a UV-LED curable digital inkjet ink containing an adhesion-promoting resin and a flexible polyurethane acrylate oligomer. The carboxyl groups in the adhesion-promoting resin form covalent bonds with the hydroxyl groups on the surface of the passivation layer during the UV curing process, and the flexible polyurethane acrylate oligomer enables the cured ink layer to have an elongation at break of 15% to 25%.

[0012] In some embodiments, a self-healing protective layer is provided on the surface of the exposed areas of the digital printing layer and the passivation layer. The self-healing protective layer is formed by coating with an aqueous polyurethane acrylate composite emulsion containing microencapsulated linseed oil. The microcapsule wall material is polyurea, the core material is linseed oil, and the microcapsule particle size is 8μm to 20μm, accounting for 6% of the coating solid content.

[0013] In some embodiments, the nano-deep pits and the aluminum plating layer are completed within a vacuum system.

[0014] In some embodiments, the production method of the high-barrier aluminized composite digitally printed corrugated cardboard box includes the following steps: S1, a hybrid aqueous emulsion capable of microphase separation is coated on the outer surface of the substrate and dried to form the base coating; S2, the surface of the base coating is subjected to selective physical etching with pure argon plasma, the polyurethane acrylate matrix is ​​preferentially removed to form the nano-pit array, and the corrosion-resistant micro-area residue is the protruding skeleton between the nano-pits. S3, high-purity aluminum is deposited on the textured surface by resistance thermal evaporation process. Aluminum atoms fill the interior of the nano-pits and fill to the bottom of the nano-pits. After solidification, aluminum studs are formed that are complementary to the morphology of the nano-pits, and the aluminum plating layer is obtained. Textured and aluminum plating are completed continuously in a vacuum environment or under vacuum protection conditions. S4, the aluminum-plated substrate is subjected to atmospheric pressure plasma online passivation under nitrogen protection. The working gas is a mixture of nitrogen and trace oxygen to form the passivation layer on the surface of the aluminum-plated layer. S5, UV-LED curable ink is sprayed and cured online on the surface of the passivation layer using a single-pass inkjet digital printer to form the digital printing layer; S6, an aqueous polyurethane acrylate composite emulsion containing microencapsulated linseed oil is coated on the surface of the exposed areas of the digital printing layer and the passivation layer, and the self-healing protective layer is formed by gradient temperature drying. S7. After cooling, the substrate is sent to the die-cutting and pressing process to produce a finished corrugated cardboard box.

[0015] (III) Beneficial Effects Compared with the prior art, the beneficial effects of the present invention are: This invention constructs a microphase separation structure in the base coating, providing a materials science basis for selective etching with pure argon plasma, and realizing the formation of self-templating ordered nano-pits. The sidewalls of the pits are based on residual polysiloxane micro-regions, and aluminum atoms are directly filled into the pits and solidified into aluminum nano-pillars that are completely complementary to the morphology of the pits. The aluminum coating layer is firmly anchored to the substrate through pure physical and mechanical interlocking, without relying on any chemical bonding or free radical reaction. This fundamentally solves the technical problem of microcrack propagation and barrier performance degradation caused by insufficient interfacial bonding in traditional aluminized corrugated cardboard boxes during folding, forming, transportation and stacking. Furthermore, the entire system uses water-based materials, the thickness of the aluminum coating layer does not exceed 50nm, and the fiber pulping rate after the cardboard box is 98.5%, meeting the requirements for recyclability. Attached Figure Description

[0016] Figure 1This is a schematic diagram of the cross-sectional structure of the substrate in Embodiment 1 of the present invention.

[0017] Figure 2 This is an enlarged structural diagram of the outer surface of the substrate in Embodiment 1 of the present invention.

[0018] Figure 3 This is a schematic diagram of the production process of Embodiment 1 of the present invention.

[0019] Figure Labels In the diagram: 1-Substrate; 2-Primer coating; 3-Aluminum plating layer; 4-Passivation layer; 5-Digital printing layer; 6-Self-healing protective layer; 7-Inner barrier coating. Detailed Implementation

[0020] To better explain and facilitate understanding of the present invention, the present invention will be described in detail below with reference to the accompanying drawings and specific embodiments.

[0021] To better understand the above technical solutions, exemplary embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present invention are shown in the drawings, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided so that the present invention can be understood more clearly and thoroughly, and that the scope of the present invention can be fully conveyed to those skilled in the art.

[0022] Example 1 like Figure 1-2 As shown, this embodiment provides a high-barrier aluminized composite digitally printed corrugated cardboard box. The base material 1 of the cardboard box is made of B-flute three-layer corrugated cardboard, and the outer surface paper of the base material 1 has a basis weight of 180g / m³. 2 Kraft paperboard, substrate 1, inner surface linerboard with a basis weight of 160g / m² 2 The kraft paperboard has a base coating layer 2, a nano-pit layer, an aluminum plating layer 3, a passivation layer 4, a digital printing layer 5, and a self-healing protective layer 6 arranged sequentially from the inside to the outside on the outer surface of the substrate 1. The inner surface of the paperboard has an inner barrier coating layer 7.

[0023] like Figure 2 As shown, the base coating 2 is a silicone-modified polyurethane-acrylate hybrid waterborne emulsion, which is applied to the face paper on the outer surface of the substrate 1 by micro-gravure roller coating, with a dry coating weight of 6 g / m². 2The hybrid aqueous emulsion, dried with hot air at 100℃, is prepared by emulsion polymerization of 25 parts by weight of aliphatic polycarbonate diol, 15 parts by weight of isophorone diisocyanate, 3 parts by weight of dimethylolbutyric acid, 20 parts by weight of butyl acrylate, 15 parts by weight of methyl methacrylate, and 8 parts by weight of hydroxyl-terminated polydimethylsiloxane, wherein the hydroxyl-terminated polydimethylsiloxane accounts for approximately 9.3% of the solid content. During the drying and film formation process, due to their low surface energy, organosilicon segments spontaneously migrate and accumulate towards the coating-air interface, forming rigid polysiloxane microregions with a diameter of 20-50 nm. The average diameter of the microregions is 34 nm, accounting for about 18% of the area. The phase difference between the microregions and the polyurethane acrylate matrix in the AFM phase diagram reaches 12.5°, and the spacing between the microregions is about 45-80 nm. The quantitative analysis data of atomic force microscopy are shown in Table 1. Meanwhile, the polyurethane acrylate segments constitute the continuous phase matrix and form multi-point hydrogen bonds with the hydroxyl groups on the paper fiber surface, thereby forming a gradient structure with rigid bonding to the paper fibers at the bottom and microphase separation and enrichment at the top.

[0024] Table 1: Quantitative Analysis of AFM Phase Diagram for Undercoat Coating like Figure 1-2 As shown, the base coating 2 also has a flexible buffer function. Its glass transition temperature is about -15℃, elongation at break is greater than 200%, surface water contact angle is 98°, and surface energy is about 28mN / m. The basic physical properties are shown in Table 2. When the cardboard is folded by the crease, it absorbs bending stress through elastic deformation, which inhibits the initiation of microcracks in the hard and brittle aluminum coating layer 3 from the root. More importantly, the bond energy of Si-O bond in the polysiloxane micro-region is about 460kJ / mol, which is significantly higher than that of CC bond (about 348kJ / mol) and CO bond (about 360kJ / mol) in the polyurethane acrylate matrix. Moreover, the polysiloxane has low surface energy and high atomic packing density, which makes the intrinsic etching rate of the micro-region under pure physical sputtering conditions significantly lower than that of the organic matrix. This provides a material science basis for "self-templating" selective etching for subsequent pure argon plasma treatment. Using the polysiloxane micro-region as an in-situ resist mask, the orderly formation of nano-pits can be guided without any additional photolithography steps.

[0025] Table 2: Basic physical properties of the microphase separation undercoat The cardboard substrate 1 with the base coating 2 is fed into a dual-chamber series vacuum device. This device has a plasma texturing chamber and an aluminizing chamber arranged sequentially along the cardboard's travel direction, connected by a differential pressure transition section. The first chamber is the plasma texturing chamber, with a working vacuum of 1-5 Pa. High-purity argon gas with a purity ≥99.99% is introduced. A 13.56MHz radio frequency power supply is used to excite glow discharge to generate high-density argon plasma. The cardboard passes uniformly through a treatment zone with an effective treatment area length of approximately 1.2m under the traction of cooling rollers. The plasma nozzle reciprocates 5 mm from the surface of the base coating 2, with a power density of 2.0-2.5 W / cm². 2 The processing speed is synchronized with the subsequent aluminum plating winding speed. Under the physical bombardment of pure argon plasma, the polyurethane acrylate matrix is ​​preferentially removed due to its high etching rate, forming a layer with a depth of 15-30 nm and an areal density of approximately 10. 10 The nano-pit array, with its corrosion-resistant polysiloxane micro-regions remaining as the raised framework between the nano-pits, exhibits a depth standard deviation of only 5 nm. The surface roughness Ra increases from 2.1 nm before treatment to 8.5 nm. The surface morphology analysis data before and after etching are shown in Table 3. The interior of the nano-pits is purified by continuous argon ion bombardment, thoroughly removing the weak boundary layer and low molecular weight contaminants. The aforementioned high-purity argon gas is ionized in the plasma to form pure Ar plasma. After pure Ar treatment, the Si / C atomic ratio on the surface of the undercoat 2 is basically consistent with that before treatment, confirming that the polysiloxane micro-regions are not destroyed and the integrity of the microphase separation template is maintained. The surface chemical state change data are shown in Table 4. Pure Ar only produces physical sputtering without introducing chemical modification. The interior of the nano-pits obtains an atomically clean intrinsic polymer surface rather than an oxide layer covered by oxygen-containing functional groups, providing an ideal interface for subsequent molecular-level close contact of aluminum atoms.

[0026] Table 3: Comparison of surface morphology before and after selective etching Table 4: XPS analysis of the surface before and after selective etching like Figure 3 As shown, after texturing treatment, substrate 1 enters the aluminizing chamber through a set of slit-type differential pressure channels. A multi-stage vacuum pump group consisting of a Roots pump and a diffusion pump is installed within the channels to smoothly transition the pressure from 1-5 Pa to 3 × 10⁻⁶ Pa. -3 Pa, an infrared reflectance spectroscopy sensor is installed in the channel to non-contactly collect the surface spectrum of the base coating 2 in real time through a sapphire optical window, monitor the degree of texture, and use it for quality traceability and anomaly alarm. The substrate 1 enters a 3×10 -3Immediately after high-vacuum aluminum plating in the Pa high-vacuum chamber, high-purity aluminum is deposited on the textured surface using a resistance thermal evaporation process. The aluminum wire purity is 99.99%, the evaporation boat temperature is 1450℃, the aluminum layer optical density OD value is 2.2, corresponding to an aluminum layer thickness of approximately 45nm. High-energy aluminum atoms directly fill the interior of the nano-pits and reach the bottom of the nano-pits. After solidification, nano-aluminum studs are formed that are completely complementary to the morphology of the nano-pits. Because aluminum is deposited directly without exposure to the atmosphere after texturing, the interior of the nano-pits remains atomically clean until the aluminum atoms fill the pits. This allows the aluminum atoms to achieve molecular-level close contact at the bottom and sidewalls of the nano-pits, maximizing van der Waals forces and metal-metal bonding. The polymer dispersion force contributes to ensure that aluminum atoms are fully filled into the deepest part of the nano-pits. After solidification, a dense aluminum pillar is formed. The aluminum layer 3 is composed of the aluminum layer and the aluminum pillar. The mechanical interlocking of the sidewalls of the nano-pits firmly locks the aluminum layer 3. The interface bonding mechanism established here is a purely physical mechanical interlock. The aluminum layer 3 and the nano-pits do not rely on any chemical bonding or free radical reaction. This fundamentally avoids the stringent requirements of free radical activity maintenance time and reaction selectivity. The process window is wider and the reliability is higher. Texturing and aluminum plating are completed continuously in the same vacuum system, ensuring cleanliness and preventing the surface of the nano-pits from being contaminated.

[0027] like Figure 3 As shown, after the aluminum-plated substrate 1 exits the vacuum chamber, it is sent to the atmospheric pressure plasma treatment area covered by a nitrogen protective curtain via the shortest path. The interval between exiting the vacuum chamber and starting plasma treatment does not exceed 30 seconds. The nitrogen protective curtain minimizes the contact between the surface of the aluminum-plated layer 3 and oxygen and water vapor in the atmosphere during the transition process. The working gas is a mixture of nitrogen and trace oxygen with a volume ratio of 99.5:0.5 and a power density of 1.5 W / cm³. 2The nozzle sweeps back and forth 4mm away from the aluminum-coated surface, with the processing speed synchronized with the aluminum-coating winding speed. A nitrogen protective curtain isolates the substrate 1 from the atmosphere along the path from the vacuum chamber exit to the plasma treatment area, eliminating the risk of the active aluminum layer being directly exposed to an uncontrolled atmosphere and instantly forming loose natural alumina. Under strictly controlled low oxygen partial pressure, the atmospheric pressure plasma simultaneously performs three functions: using active oxygen atoms in the plasma to grow a 2-3nm thick, precisely stoichiometric, and dense γ-Al2O3 (gamma alumina) type passivation layer 4 on the surface of the aluminum-coated layer 3, effectively preventing water vapor and corrosive gases from eroding the aluminum-coated layer 3 and preventing white spot hydration oxidation and gloss decay during transfer and inter-process storage; high-density hydroxyl groups naturally form on the surface of the passivation layer 4, significantly increasing the surface energy of the aluminum-coated layer 3 from approximately 30 mN / m to 58-62. mN / m provides a high surface energy chemical anchor for subsequent UV inkjet inks; removes trace amounts of organic contaminants such as vacuum pump oil vapor that may be adsorbed on the aluminum surface after aluminizing; after 14 days of accelerated aging at high temperature and humidity, the sample with passivation layer 4 has a gloss retention rate of 97.6% and a peel strength retention rate of 92.9%, while the comparative sample without passivation layer 4 has only 72.9% and 83.3%, respectively. The data on accelerated aging and inter-process temporary storage stability are shown in Table 5.

[0028] Table 5: Accelerated Aging and Inter-process Temporary Stability like Figure 2-3 As shown, the cardboard substrate 1 with the passivation layer 4 is fed into the digital printing station via a buffer storage rack with a storage depth of 8m. This allows the digital printing speed to be independently adjusted within the range of 90% to 110% of the metallization speed, achieving speed decoupling from the vacuum metallization process. Digital printing uses a single-pass inkjet digital printer to spray and cure UV-LED curable ink on the surface of the passivation layer 4, forming a digital printing layer 5. The ink is a UV-LED curable digital inkjet ink containing adhesion-promoting resin and flexible polyurethane acrylate oligomers. The carboxyl groups in the adhesion-promoting resin and the abundant hydroxyl groups on the surface of the passivation layer 4 undergo acid-catalyzed esterification condensation to form covalent bonds during UV curing. The flexible polyurethane acrylate oligomers impart a breaking elongation of 15%-25% to the cured ink layer to accommodate subsequent creasing and folding deformation of the cardboard. After printing, the cardboard undergoes a constant temperature resting stage at 40℃ with a 0.5°C curing rate. Running at a speed of m / min for about 5 minutes, the secondary initiation temperature of the residual photoinitiator in the UV ink is about 70°C. Therefore, it does not trigger a new curing reaction, but it is sufficient to allow the incompletely reacted flexible oligomer segments to gain molecular freedom of movement and undergo conformational rearrangement, gradually releasing the internal stress generated by curing shrinkage. At the same time, under low temperature and anhydrous conditions, the long-term contact between the carboxyl groups in the resin and the hydroxyl groups on the surface of the passivation layer 4 promotes the esterification equilibrium to slowly move towards the formation of strong ester bonds, further enhancing the chemical adhesion of the digital printing layer 5 without introducing additional curing steps.

[0029] like Figure 2 As shown, the self-healing protective layer 6 is made of a water-based polyurethane acrylate composite emulsion containing microencapsulated linseed oil, which is applied to the entire outer surface of the exposed areas of the digital printing layer 5 and the passivation layer 4 by a micro-gravure roller coating method, with a dry coating amount of 2.5 g / m². 2 The microcapsule wall material is polyurea, and the core material is linseed oil. The particle size is 8-20μm, the median particle size D50 is 12μm, and it accounts for 6% of the coating solid content. The drying process adopts a gradient temperature change process: the first stage is 50℃ hot air drying for 2 minutes, which allows most of the moisture in the coating to evaporate slowly, avoiding rapid skinning on the surface, which would lead to internal moisture retention and uneven volume shrinkage; the second stage is 60℃ hot air drying for 3 minutes, which completes the evaporation of the remaining moisture and the formation of the coating film. The actual surface temperature of the cardboard does not exceed 55℃ during the entire drying process. The drying temperature of 60℃ is much lower than the thermal activation polymerization temperature of linseed oil, the core material of the microcapsules, which is about 100℃. This avoids premature rupture and failure of the microcapsules during manufacturing. It is also lower than the secondary reaction temperature of the residual photoinitiator and monomers in the UV-LED curing ink, which is about 70℃. This ensures that the ink layer does not become brittle or yellow during the drying process of the protective layer. In the exposed area of ​​the passivation layer 4, the protective layer forms hydrogen bonds and chemical bonds through the polar groups on the surface of the passivation layer 4. In the area of ​​the digital printing layer 5, it forms an interpenetrating network structure with the flexible oligomers in the ink layer, which anchors the protective layer. This ensures uniform interfacial bonding strength of the protective layer across the entire printing surface and eliminates the overlap that may occur between the aluminum-plated area and the printing area when applying coatings in different areas. For seam defects, when microcracks are generated in corrugated cardboard boxes due to scratches or slight collisions during subsequent processing, transportation, or use, the stress at the crack tip causes the microcapsules to rupture and release linseed oil. The linseed oil undergoes an oxidative polymerization and cross-linking reaction under the action of oxygen in the air to form a continuous solid film that fills the crack. The self-healing efficiency over time is shown in Table 6. The crack healing rate reaches 75% within 24 hours at room temperature and 81% within 48 hours. The oxygen permeability of the unrepaired sample after artificial scratching deteriorates sharply from 4.5 to 18.6, while it recovers to 5.1 after 24 hours of self-healing and further recovers to 4.7 after 48 hours of self-healing, approaching the level of no damage. The barrier performance data before and after self-healing are shown in Table 7.

[0030] Table 6: Self-repair efficiency over time Table 7: Barrier Performance Before and After Self-Healing like Figure 2 As shown, the inner barrier coating 7 is coated with a water-based polyvinylidene chloride (PVDC) emulsion onto the inner surface of the corrugated cardboard substrate 1, with a dry coating amount of 4 g / m². 2After being dried at 55℃ using a combination of far-infrared and hot air, PVDC has extremely low water vapor transmission rate (WVTR) and oxygen transmission rate (OTR). Together with the outer aluminum-plated layer 3, it forms double-sided protection, ensuring that the carton can resist the intrusion of external moisture in a cold and humid environment, while also preventing moisture from seeping out of the internal contents. This allows the corrugated cardboard to maintain its structural strength and barrier properties throughout the cold chain transportation process.

[0031] During use, the flexible base coating 2 absorbs folding stress through elastic buffering, and the mechanical interlocking of the nano-pits and the aluminum plating layer 3 allows the aluminum studs to undergo micro-rotation and sliding within the nano-pits, thereby dissipating energy, preventing the initiation of macroscopic cracks, and ensuring that the aluminum layer remains tightly adhered to the substrate 1 after deformation without producing through-hole defects. Comparison data on folding performance and barrier performance are shown in Tables 8 and 9. After folding the pressure line 90°, the microcrack density of the aluminum plating layer 3 in the pressure line area is only 0.3 cracks / cm, while the untextured comparative sample has a density as high as 1.2 cracks / cm; the oxygen permeability is 4.5 cm. 3 / m 2 • 24h • 0.1MPa, after folding, it only increased to 4.7, with a change rate of only +4.4%, while the OTR of the comparison sample increased from 5.2 to 8.5 after folding, with a change rate as high as +63.5%; after repulping according to the pulping recycling standard process, the fiber pulping rate was 98.5%, and the whiteness of the recycled paper decreased by only 1.7 percentage points. The comprehensive performance is summarized in Table 10.

[0032] Table 8: Comparison of Folded Microcrack Density Table 9: Barrier Performance and Barrier Retention Rate After Folding Table 10: Summary of Overall Performance The substrate 1 prepared in this embodiment was subjected to a 180° peel test at a peel speed of 50 mm / min and a sample width of 25 mm. Each sample point was measured 10 times repeatedly. The peel strength reached 4.2 N / cm with a standard deviation of 0.35. The coefficient of variation was 8.3%, and the peeling curve was sawtooth-shaped. The aluminum studs in the aluminum plating layer 3 broke one by one. Scanning electron microscopy was performed on the peeled base layer 2 and aluminum plating layer 3. The base layer 2 showed the fracture surface remaining after the aluminum stud roots broke. The aluminum plating layer 3 showed the corresponding nano-pits and broken aluminum stud residues. This morphological pairing directly confirmed the existence of the mechanical interlocking structure. X-ray photoelectron spectroscopy analysis showed that no significant Al element residue was found in the peeled base layer 2, while the aluminum plating layer 3 showed C, O, and Si characteristic signals from the base layer 2 in addition to Al. This indicates that the aluminum studs were pulled out of the nano-pits and remained in the aluminum plating layer 3. The fracture occurred in the base layer 2 body where the aluminum stud roots were located. It belongs to the cohesive failure of the base layer 2, not the debonding of the aluminum plating layer 3 and the base layer 2. The mechanical interlocking strength has exceeded the cohesive strength of the base layer 2 body.

[0033] A comparative experiment was conducted on the base coating 2 and the homogeneous coating of the substrate 1 prepared in this embodiment. The homogeneous coating used a conventional polyurethane acrylate emulsion without terminal hydroxyl polydimethylsiloxane segments as the base coating 2, with an equal amount of methyl methacrylate to make up the solid content. After pure argon plasma treatment and immediate aluminum plating, just like in this embodiment, scanning electron microscopy showed that the surface of the homogeneous coating after pure argon plasma treatment only formed random shallow depressions with a depth of 5-10 nm, and there was no identifiable ordered array of nano-pits. Atomic force microscopy phase diagrams showed that the entire surface had a uniform single-phase structure with no microphase separation characteristics. The peel strength was only 2.6 N / cm, about 62% of that in Example 1. The peel curve showed a smooth interface debonding characteristic. After peeling, the aluminum layer surface was smooth and featureless. Only a small amount of pull-out material remained on the surface of the base coating 2. After folding the pressure line 90°, the microcrack density was 0.8 cracks / cm, which was significantly higher than 0.3 cracks / cm in Example 1. The comparative data are shown in Table 11. This indicates that by simply relying on random physical coarsening by plasma without the aid of a microphase separation template, the peel strength is approximately 2.6 N / cm. The upper limit of N / cm cannot be broken through to the 4.2 N / cm level dominated by mechanical interlocking. Therefore, the microphase separation base coating 2 is a material science prerequisite for achieving selective etching and ordered nano-pit arrays and cannot be omitted.

[0034] Table 11: Comparison of microphase-separated base coating and homogeneous coating For the substrate 1 prepared in this embodiment, a comparative experiment was conducted between a chamber-type series design and delayed aluminum deposition. The delayed aluminum deposition comparative experiment used the same microphase-separated undercoat 2 and pure argon plasma treatment conditions as in this embodiment. However, after the textured sample was removed from the vacuum chamber and exposed to the atmospheric environment (25°C, 50%RH) for 30 minutes, it was then placed back into the aluminum deposition chamber for aluminum deposition. X-ray photoelectron spectroscopy analysis showed that the O / C atomic ratio of the textured surface in delayed aluminum deposition increased from 0.35 in immediate aluminum deposition to 0.42, and obvious adsorbed water characteristic peaks were detected. This indicates that water vapor adsorption and organic pollutant redeposition occurred on the clean surface of the nano-pits in the atmosphere. The peel strength decreased from 4.2 N / cm in immediate aluminum deposition to 2.9. The N / cm decreased by about 31%, the peeling curve returned to the interface debonding characteristics, the aluminum pin pull-out characteristics disappeared, and scanning electron microscopy showed that only a small number of irregular aluminum fragments remained on the surface of the delayed aluminum plating layer, with no identifiable aluminum pin array. The comparative data are shown in Table 12. This indicates that the clean nano-pit surface formed by texturing has extremely strong time sensitivity. Once exposed to the atmosphere, it will be passivated due to the adsorption of water vapor and pollutants. Aluminum atoms cannot effectively fill the bottom of the nano-pit to form complete aluminum pins. It is necessary to complete the aluminum plating immediately in a vacuum environment through a segmented series design to ensure the complete filling of aluminum pins and the mechanical interlocking effect. The segmented equipment solves the process window connection problem from vacuum in texturing to high vacuum in immediate aluminum plating.

[0035] Table 12: Comparison of Immediate Aluminum Plating and Delayed Aluminum Plating The effects of organosilicon content and plasma working gas type on microphase separation morphology, selective etching effect, and interfacial bonding strength were systematically investigated on the substrate 1 prepared in this embodiment. Base coating 2 was prepared using organosilicon-modified polyurethane acrylate hybrid emulsions with hydroxyl-terminated polydimethylsiloxane (PDM) content of 3%, 5%, 8%, 9.3%, and 12%, respectively, with the remaining component proportions the same as in this embodiment. Methyl methacrylate was used to compensate for the solid content difference. The substrates were treated with pure argon plasma under the same conditions as in this embodiment and immediately aluminum was deposited. Quantitative analysis data using atomic force microscopy are shown in Table 13. When the PDM content was 3%, the average micro-area diameter was only 12 nm, the area ratio was 4%, and the phase diagram phase difference was 3.2°, indicating insufficient phase separation. This resulted in only random shallow depressions being formed during subsequent etching, with a peel strength of 2.5 N / cm and interfacial debonding as the failure mode. When the content was 5%, the micro-area size increased to 20 nm, the area ratio was 10%, and the phase difference was 7.8°, indicating preliminary etching selectivity and an increase in peel strength to 3.2 N / cm. The peel strength was 4.2 N / cm at a content of 8%-12%, forming a clear microphase separation structure with a micro-region diameter of 30-48 nm, an area ratio of 16%-26%, and a phase difference of 11.0°-16.1°. After etching, a uniform array of nano-pits was formed. The peel strength reached the optimal value of 4.2 N / cm at a content of 9.3%, and the peel strength was cohesive failure caused by the pull-out of aluminum studs. When the content exceeded 12%, the polysiloxane micro-regions began to connect into sheets. After etching, the residual skeleton was too wide, the area ratio of nano-pits decreased, and the peel strength dropped back to 3.8 N / cm. The peel strength data for different organosilicon contents are shown in Table 14. The optimal range for hydroxyl-terminated polydimethylsiloxane content is about 8%-9.3%, which balances the clarity of phase separation and the area ratio of nano-pits.

[0036] Table 13: Microphase separation morphology under different PDMS-OH contents Table 14: Peel strength at different PDMS-OH contents A base coating 2 with a hydroxyl-terminated polydimethylsiloxane content of 9.3% was used. Plasma treatment was performed using pure Ar, Ar / O2 (volume ratio 95:5), and pure O2 as working gases, respectively, at the same power density and processing time. Under pure Ar conditions, the plasma only had a physical sputtering effect on the surface of the base coating 2. The Si-O bond energy of the polysiloxane micro-region was approximately 460 kJ / mol, significantly higher than that of the C-C bonds (approximately 348 kJ / mol) and CO bonds (approximately 360 kJ / mol) in the matrix. Furthermore, the polysiloxane had a low surface energy and high atomic packing density. Under pure physical bombardment, the intrinsic sputtering yield was significantly lower than that of the organic matrix. The matrix was preferentially etched away, while the polysiloxane micro-regions were completely preserved as a framework. The edges of the nano-pits were clear, and the bottom surface was clean. The depth of the nano-pits was 22 nm, and the areal density was 2.0 × 10⁻⁶. 10 pcs / cm 2 XPS analysis showed that the Si / C atomic ratio on the surface of the base coating 2 after pure Ar treatment was basically the same as before treatment, confirming that the polysiloxane microregions were not destroyed. The peel strength reached 4.2 N / cm, and the failure mode was the pull-out of aluminum pins. Under Ar / O2 conditions, the introduction of oxygen changed the plasma from pure physical sputtering to a mixed mode of physical sputtering and chemical etching. Active oxygen atoms simultaneously chemically etched both the substrate and the polysiloxane microregions. Although the latter reacted more slowly due to the inertness of the Si-O bond, the difference in the overall etching rate between the two phases was significantly reduced. SEM observation showed that the pit boundaries became blurred, the selectivity decreased, the pit depth decreased to 14 nm, and the areal density decreased to 1.5 × 10⁻⁶. 10 pcs / cm 2 XPS analysis showed that the Si / C atomic ratio decreased by about 15% before treatment, some polysiloxane micro-regions were oxidized and etched, the peel strength dropped to 3.2 N / cm, a decrease of about 24% compared with pure Ar, and the peel curve showed interfacial debonding components. Under pure O2 conditions, chemical etching was absolutely dominant, the physical sputtering effect was negligible, and active oxygen atoms indiscriminately etched all organic components. The polysiloxane micro-regions and the matrix were removed simultaneously, and the microphase separation template was completely destroyed. SEM observation showed that there were no identifiable micro-region morphology residues on the surface, only a uniform oxide roughening layer was formed, and the pit array disappeared. XPS analysis showed that the Si / C atomic ratio decreased by about 40% before treatment, the O / C atomic ratio increased significantly from 0.35 in pure Ar to 0.53, a large number of oxygen-containing functional groups and silicon oxide materials were generated on the surface, and the peel strength was only 2.8 N / cm, a decrease of about 33% compared with pure Ar. The destruction mode completely degenerated to interfacial debonding. The comparison data of surface chemical state and etching effect are shown in Tables 15 and 16.

[0037] Table 15: Surface chemical states (XPS) under different working gases Table 16: Etching effect and peel strength under different working gases Note: Under pure O2 conditions, the chemical coarsening is uniform, and there is no identifiable ordered pit structure. The pit depth and areal density are not applicable.

[0038] The above comparative data reveals three irreplaceable roles of pure Ar physical bombardment: only pure Ar can maintain the intrinsic sputtering yield difference between the two phases, completely "transferring" the microphase separation structure into an ordered nano-pit array, and the oxygen-containing gas reduces the selectivity window due to the introduction of chemical etching; pure Ar does not introduce chemical modification during etching, and the nano-pits obtain an atomically clean intrinsic polymer surface, enabling subsequent aluminum atoms to achieve molecular-level close contact, maximizing the contribution of van der Waals forces and dispersion forces, while the oxygen-containing functional groups and oxide layer introduced by the oxygen-containing plasma become the interface isolation layer; only pure Ar can completely preserve the polysiloxane microregions, maintaining the integrity of the microphase separation template. Under pure O2 conditions, the microregions are largely oxidized and removed, causing the template to disappear. The improvement from 2.8 N / cm to 4.2 N / cm comes entirely from the qualitative change from "non-selective uniform oxidation coarsening" to "selective ordered nano-pit array plus atomically clean interface", and this qualitative change only occurs when using pure Ar.

[0039] In summary, the experimental data systematically demonstrate the effectiveness and irreplaceability of the technical solution in this embodiment from multiple perspectives: SEM morphology pairing and XPS elemental analysis of the peel test confirmed the existence of the mechanical interlocking structure; the aluminum pin pull-out failure mode proved that the interfacial bonding strength exceeded the cohesive strength of the base coating 2, indicating that the interface is no longer a performance bottleneck; the organosilicon content gradient experiment determined that the content of hydroxyl-terminated polydimethylsiloxane was approximately 8%-9.3% as the optimal range, within which microphase separation was clear, the nano-pit array was uniform, and the peel strength reached its maximum value of 4.2. The gas type comparison experiment revealed three irreplaceable roles of pure Ar physical bombardment in achieving selective etching: maintaining the intrinsic sputtering yield difference between the two phases to transfer the microphase separation structure into an ordered nano-pit array; not introducing chemical modification to maintain atomic-level cleanliness inside the nano-pits; and completely preserving the polysiloxane microregions to maintain template integrity. The improvement from 2.8 N / cm to 4.2 N / cm is entirely due to the qualitative change from non-selective uniform oxidation coarsening to selective ordered nano-pit array plus atomically clean interface. The homogeneous coating comparison experiment proved that the peel strength has an upper limit of about 2.6 N / cm without microphase separation template, which cannot be broken through to the mechanical interlocking level. The delayed aluminizing comparison experiment proved that the textured clean surface has extremely strong time sensitivity. It is preferable to complete the aluminizing immediately through a cavity-type series design. The three factors work together to achieve a reduction from 1.1 N / cm of debonding between the aluminum layer and the base coating 2 at the traditional interface to 4.2 N / cm of cohesive pull-out of the aluminum studs. The failure mode of N / cm was changed, the bonding strength was increased to about 3.8 times, the microcrack density after creasing and folding decreased from 1.2 cracks / cm to 0.3 cracks / cm, and the oxygen permeability change rate narrowed from +63.5% to +4.4%. This fundamentally solved the problem of microcrack propagation and barrier performance degradation in aluminized corrugated boxes caused by insufficient interfacial bonding during folding, forming and transportation stacking.

[0040] like Figure 3 As shown, a production method for a high-barrier aluminized composite digitally printed corrugated cardboard box includes the following steps: Primer coating station: A silicone-modified polyurethane-acrylate hybrid emulsion is coated onto the outer surface of corrugated cardboard substrate 1 using a micro-gravure roller coating method, with a dry coating amount of 6 g / m². 2 The microphase separation flexible base coating is formed by drying with hot air at 100℃.

[0041] Inner coating station: PVDC water-based emulsion is coated onto the inner surface of corrugated cardboard substrate 1 using a roller coating method, with a dry coating amount of 4 g / m². 2 The inner barrier coating is formed by drying with far-infrared and hot air at 55℃.

[0042] Pre-drying station: Before substrate 1 enters the vacuum system, the moisture content of the paperboard is controlled to below 3% by the online infrared pre-drying section to avoid excessive gas release in the vacuum chamber.

[0043] Plasma texturing process: Substrate 1 is continuously fed into the first chamber of a dual-chamber series vacuum device. High-purity argon gas is introduced under a working vacuum of 1-5 Pa. Argon plasma is generated by exciting glow discharge using a radio frequency power supply. This plasma selectively etches the surface of the microphase-separated flexible undercoat 2, preferentially removing the polyurethane acrylate matrix to form a layer with a depth of 15-30 nm and an areal density of approximately 2.0 × 10⁻⁶. 10 pcs / cm 2 The nano-pit array, with corrosion-resistant polysiloxane micro-regions remaining as the raised framework between the nano-pits.

[0044] Instant aluminum plating station: Substrate 1 enters the second chamber from the first chamber via a differential pressure transition section. Within this transition section, a multi-stage vacuum pump unit smoothly transitions the pressure from 1-5 Pa to 3 × 10⁻⁶ Pa. -3 Pa; After the substrate 1 enters the second cavity, high-purity aluminum is deposited on the textured surface immediately by resistance thermal evaporation process. The aluminum wire purity is 99.99%, the evaporation boat temperature is 1450℃, the aluminum layer optical density OD value is 2.2, corresponding to an aluminum layer thickness of about 45nm. High-energy aluminum atoms fill the interior of the nano-pits and fill to the bottom of the nano-pits. After solidification, aluminum nano-pillars that are completely complementary to the morphology of the nano-pits are formed. Textured and aluminum plating are completed continuously in the same vacuum system with an interval of no more than 10 seconds.

[0045] Online passivation stage: After the aluminum-plated substrate 1 exits the vacuum chamber, it immediately undergoes atmospheric pressure plasma treatment under a nitrogen protective curtain. The working gas is a mixture of nitrogen and trace oxygen (volume ratio 99.5:0.5) with a power density of 1.5 W / cm³. 2 The nozzle sweeps back and forth 4 mm away from the aluminum-plated surface to form a dense γ-Al2O3 passivation layer 4 with a thickness of 2-3 nm on the aluminum surface, while increasing the surface energy to 58-62 mN / m.

[0046] Digital printing and relaxation station: After the substrate 1 is decoupled from the speed of the buffer storage rack with a storage depth of 8 m, it is printed and cured online on the surface of the passivation layer 4 by a single-pass inkjet digital printer to form the digital printing layer 5. After printing, the substrate 1 enters the 40℃ constant temperature relaxation section and runs at a speed of 0.5 m / min for about 5 minutes to allow the unreacted flexible oligomer chain segments in the UV-cured ink layer to rearrange their conformation and release internal stress. At the same time, under low temperature and anhydrous conditions, the esterification reaction between the carboxyl groups in the resin and the hydroxyl groups on the surface of the passivation layer 4 is promoted.

[0047] Protective coating station: A water-based polyurethane acrylate composite emulsion containing microencapsulated linseed oil is coated onto the entire outer surface of the exposed areas of digital printing layer 5 and passivation layer 4 using a micro-gravure roller coating method. The dry coating amount is 2.5 g / m². 2The drying process uses a gradient temperature change process. The first stage is 50°C hot air drying for 2 minutes to slowly evaporate most of the moisture in the coating. The second stage is 60°C hot air drying for 3 minutes to complete the evaporation of the remaining moisture and the formation of the coating film, forming a self-healing protective layer.

[0048] Post-processing station: After the substrate 1 with the protective coating is cooled to room temperature by the cooling roller, it is sent to the die-cutting and creasing process. After die-cutting, creasing, grooving, and nailing or gluing, the corrugated cardboard box is made into a finished product.

[0049] Example 2

[0050] The main difference between this embodiment and Embodiment 1 is that the flexible base coating 2 uses a silane coupling agent modified nano-silica assisted microphase separation structure to replace the organosilicon microphase separation structure, so as to reduce the raw material cost and improve the surface hardness of the base coating 2. The remaining structure, process steps and parameters are the same as those in Embodiment 1.

[0051] Flexible base coating 2 uses a modified nano-silica polyurethane acrylate hybrid waterborne emulsion, which is applied to the outer surface paper by micro-gravure roller coating, with a dry coating weight of 6 g / m². 2 After being dried with hot air at 100℃, the hybrid aqueous emulsion was prepared by emulsion polymerization of the following components: 25 parts by weight of aliphatic polycarbonate diol, 15 parts by weight of isophorone diisocyanate, 3 parts by weight of dimethylolbutyric acid, 20 parts by weight of butyl acrylate, 15 parts by weight of methyl methacrylate, and 12 parts by weight of nano-silica sol modified with γ-aminopropyltriethoxysilane. The modified nano-silica accounts for about 7.5% of the solid content of the emulsion.

[0052] The modification method of γ-aminopropyltriethoxysilane is as follows: γ-aminopropyltriethoxysilane is diluted to 5% by mass with a mixed solvent of ethanol and water in a volume ratio of 9:1, and added to nano-silica sol. The amount of silane coupling agent is 3% of the mass of nano-silica. The mixture is stirred and hydrolyzed at 50°C for 2 hours to obtain modified nano-silica sol with amino and ethoxy active groups grafted on its surface. During emulsion polymerization, the ethoxy groups on the surface of the modified nano-silica react with the isocyanate groups at the chain ends of the polyurethane prepolymer to form covalent bonds, anchoring the nano-silica particles in the polymer network through chemical bonds, thus completely solving the problem of physical blend particles falling off under plasma bombardment.

[0053] During the drying and film formation process, covalently anchored silica nanoparticles are chemically bonded to the polymer network, forming uniformly dispersed hard nanoparticle aggregates in the coating. The polyurethane-acrylate segments constitute the continuous phase matrix. Due to the significant modulus and chemical inertia differences between the silica nanoparticle aggregates and the organic matrix, the polyurethane-acrylate matrix is ​​preferentially etched away under pure argon plasma bombardment. The silica nanoparticle aggregates, due to the high bond energy of the Si-O bonds and covalent anchoring, exhibit a low etching rate and do not detach, leaving behind a raised framework between nanopits, forming a depth of 12-25 nm and an areal density of approximately 1.5 × 10⁻⁶. 10 pcs / cm 2 Array of nano-pits.

[0054] After immediate aluminizing under the same conditions as in Example 1, the 180° peel strength reached 3.8 N / cm. The peel failure mode was cohesive failure due to the pull-out of aluminum studs. Post-peel SEM observation confirmed the existence of the mechanical interlocking structure. The nano-pit morphology was regular, and no defects caused by particle shedding were observed. After folding the wire 90°, the microcrack density was 0.35 cracks / cm, and the oxygen permeability was 4.8cm. 3 / m 2 ·24h·0.1MPa.

[0055] Compared to Example 1, the peel strength of this example is slightly lower, mainly because the dispersion uniformity and phase separation of the nano-silica particles in the coating are not as good as the microphase separation structure formed by the self-migration of organosilicon segments, resulting in slightly lower nano-pit surface density and depth. However, the cost of the modified nano-silica raw material is only about 15% of that of hydroxyl-terminated polydimethylsiloxane, and the surface hardness of the coating is increased by about 30%. The peel strength is still about 3.5 times that of the untextured comparative sample (1.1 N / cm), giving it a competitive advantage in cost-sensitive applications with high scratch resistance requirements.

[0056] The other structures and production methods in this embodiment are the same as in Embodiment 1, and will not be repeated here.

[0057] Example 3

[0058] The main difference between this embodiment and Embodiment 1 is that plasma texturing and aluminizing use separate chamber equipment instead of a dual-chamber series integrated equipment to meet the post-installation requirements of the texturing process in existing independent aluminizing production lines. The remaining structure and process parameters are the same as in Embodiment 1.

[0059] The cardboard substrate 1 with the microphase-separated base coating 2 is first fed into a separate medium-vacuum plasma texturing device. The working vacuum of the texturing chamber is 1-5 Pa, and high-purity argon gas is introduced. Glow discharge is excited using a 13.56 MHz radio frequency power supply with a power density of 2.0-2.5 W / cm². 2The processing speed is about 3 m / min. After texturing, the cardboard is immediately wound up at the cavity outlet. During the winding process, the texturized surface does not come into contact with any roller surface. A suspended winding method can be used. The winding tension is controlled at 50-80 N / m to avoid crushing the nano-pitted structure. After winding, the roll is vacuum sealed and packaged and then transferred to the aluminizing production line.

[0060] Before aluminizing, the roll is unwound in a vacuum environment. The cardboard enters the high-vacuum aluminizing chamber through a differential pressure transition section. High-purity aluminum is deposited on the textured surface through a resistance thermal evaporation process. The aluminum layer has an optical density OD value of 2.2, corresponding to an aluminum layer thickness of approximately 45 nm. The total interval from the first contact of the textured surface with the low-pressure environment to the completion of aluminizing is controlled within 60 minutes. Vacuum-sealed packaging ensures that the nano-pitted surface only comes into contact with a low-pressure inert environment of ≤100 Pa during transportation, and the adsorption of water vapor and organic pollutants is controlled at an acceptable level.

[0061] Testing revealed that the 180° peel strength of this embodiment reached 3.5 N / cm, a decrease of approximately 17% compared to 4.2 N / cm in Example 1, but still an increase of approximately 3.2 times compared to the 1.1 N / cm of the untextured control sample. The peel failure mode was mixed failure, with a microcrack density of 0.45 cracks / cm after 90° folding at the crease, and an oxygen permeability of 4.9 cm. 3 / m 2 ·24h·0.1MPa.

[0062] Compared with Example 1, the reason for the decrease in peel strength is that during the transfer process, the surface of the nano-pits under vacuum sealing environment underwent a small amount of residual water vapor adsorption and slight physical deformation, which partially weakened the effect of close contact of the clean interface. However, the advantage of this embodiment is that the plasma texturing equipment can be installed as an independent module at the front end of the existing aluminizing production line without replacing the entire vacuum aluminizing equipment. The equipment modification investment is only about 30% of the dual-cavity series integrated solution, which is suitable for the technical upgrade and transformation of existing aluminizing production lines.

[0063] The other structures and production methods in this embodiment are the same as in Embodiment 1, and will not be repeated here.

[0064] In the description of this invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this invention, "a plurality of" means two or more, unless otherwise explicitly specified.

[0065] In this invention, unless otherwise explicitly specified and limited, the terms "installation," "connection," "linking," and "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. Those skilled in the art can understand the specific meaning of the above terms in this invention according to the specific circumstances.

[0066] In this invention, unless otherwise explicitly specified and limited, "above" or "below" the second feature can mean that the first and second features are in direct contact, or that they are in indirect contact through an intermediate medium. Furthermore, "above," "over," or "on top" the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply indicates that the first feature is at a higher horizontal level than the second feature. "Below," "below," or "beneath" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply indicates that the first feature is at a lower horizontal level than the second feature.

[0067] In the description of this specification, the terms "one embodiment," "some embodiments," "embodiment," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0068] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make modifications, alterations, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. A high-barrier aluminized composite digitally printed corrugated cardboard box, comprising a substrate (1), an inner barrier coating (7), a base coating (2), an aluminized layer (3), a passivation layer (4), and a digital printing layer (5), characterized in that: The substrate (1) is corrugated cardboard; The inner barrier coating (7) is constructed as a polyvinylidene chloride aqueous emulsion and is coated on the inner surface of the substrate (1). The base coating (2) is constructed as an organosilicon-modified polyurethane acrylate hybrid waterborne emulsion and is applied to the outer surface of the substrate (1) on the side opposite to the inner barrier coating (7). The surface of the base coating (2) is selectively etched with pure argon plasma to form a nano-pit array; The aluminum plating layer (3) is deposited on the surface of the nano-pits and the aluminum plating layer (3) is anchored on the nano-pits; The passivation layer (4) is disposed on the surface of the aluminum plating layer (3); The digital printing layer (5) is disposed on the surface of the passivation layer (4).

2. The high-barrier aluminized composite digitally printed corrugated cardboard box according to claim 1, characterized in that, The base coating (2) serves as an in-situ anti-corrosion mask during pure argon plasma treatment, enabling self-templating selective etching.

3. The high-barrier aluminized composite digitally printed corrugated cardboard box according to claim 1, characterized in that, The organosilicon segments in the base coating (2) are hydroxyl-terminated polydimethylsiloxane, which account for 8% to 9.3% of the emulsion solid content.

4. The high-barrier aluminized composite digitally printed corrugated cardboard box according to claim 1, characterized in that, The depth of the nano-pits is 15nm to 30nm, and the areal density is 10. 9 pcs / cm 2 Up to 10 10 pcs / cm 2 Magnitude.

5. The high-barrier aluminized composite digitally printed corrugated cardboard box according to claim 1, characterized in that, The aluminum layer thickness of the aluminum plating layer (3) is 40 nm to 55 nm.

6. The high-barrier aluminized composite digitally printed corrugated cardboard box according to claim 1, characterized in that, The passivation layer (4) has a thickness of 2 nm to 3 nm and the surface energy of the passivation layer (4) is increased to 58 mN / m to 62 mN / m.

7. The high-barrier aluminized composite digitally printed corrugated cardboard box according to claim 1, characterized in that, The digital printing layer (5) is formed by inkjet printing using a UV-LED curable digital inkjet printer containing an adhesion-promoting resin and a flexible polyurethane acrylate oligomer.

8. The high-barrier aluminized composite digitally printed corrugated cardboard box according to claim 1, characterized in that, A self-healing protective layer (6) is provided on the surface of the exposed areas of the digital printing layer (5) and the passivation layer (4). The self-healing protective layer (6) is formed by coating with a water-based polyurethane acrylate composite emulsion containing microencapsulated linseed oil.

9. The high-barrier aluminized composite digitally printed corrugated cardboard box according to claim 1, characterized in that, The nano-deep pit and the aluminum plating layer (3) are completed in a vacuum system.

10. A method for producing a high-barrier aluminized composite digitally printed corrugated cardboard box according to any one of claims 1 to 9, characterized in that, Includes the following steps: S1, a hybrid aqueous emulsion capable of microphase separation is coated on the outer surface of the substrate (1), and the base coating (2) is formed by drying. S2, the surface of the base coating (2) is subjected to pure argon plasma selective physical etching, the polyurethane acrylate matrix is ​​preferentially removed to form the nano-pit array, and the corrosion-resistant micro-area residue is the protruding skeleton between the nano-pits. S3, high-purity aluminum is deposited on the textured surface by resistance thermal evaporation process. Aluminum atoms fill the interior of the nano-pits and fill to the bottom of the nano-pits. After solidification, aluminum studs are formed that are complementary to the morphology of the nano-pits, and the aluminum plating layer (3) is obtained. Textured and aluminum plating are completed continuously in a vacuum environment or under vacuum protection conditions. S4, the aluminum-plated substrate (1) is subjected to atmospheric pressure plasma passivation under nitrogen protection. The working gas is a mixture of nitrogen and trace oxygen to form the passivation layer (4) on the surface of the aluminum-plated layer (3). S5, UV-LED curable ink is sprayed and cured online on the surface of the passivation layer (4) using a single-pass inkjet digital printer to form the digital printing layer (5). S6, an aqueous polyurethane acrylate composite emulsion containing microencapsulated linseed oil is coated on the surface of the exposed areas of the digital printing layer (5) and the passivation layer (4), and the self-healing protective layer (6) is formed by gradient temperature drying. S7, the substrate (1) is cooled and then sent to the die-cutting and pressing process to produce a finished corrugated cardboard box.